Tingkat Loyalitas Pelanggan Berbasis Harga, Kualitas Pelayanan, dan Kepuasan Konsumen di Pasar Saudara Swalayan Jepara - P, Purwati; Kamila, Rif’ana Naila; R, Rismawati; Nuraini, Revi Khorirotun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the effect of price, service quality, and customer satisfaction on the level of customer loyalty in the Saudara Swalayan Jepara market. This type of research uses a quantitative approach with a survey method, which is a type of research approach that uses numerical data collection to measure certain variables and analyze the relationship between variables with statistical techniques. The method used in this research is a questionnaire method distributed to 60 respondents. The population in this study were Customers / Customers of Saudara Swalayan. The statistical analysis method used is validity test, reliability test, correlation test, classical assumption test, and linearity test with SPSS application tools. The results showed that the price variable (X1) had a significant effect on customer loyalty (Y), while the service quality variable (X2) and customer satisfaction (X3) had no significant effect on customer loyalty (Y).